Useful Plants Used by Tajpuria Community of Jhapa District, Nepal (Patan Pragya, 2025)
Local plant resources are important in the livelihood of various ethnic communities in Nepal. The aim of the study is to record the useful plants used by Tajpuriya community of Jhapa district, eastern Nepal. The study documented 38 useful plants from 28 families and 36 genera. The family Malvaceae was documented as dominant. Trees were recorded as dominant (39%), followed by herbs (32%) and shrubs (29%). The major source of these useful plants was forest (66%), 18% were cultivated and 16% were both wild as well as cultivated. These documented plant species were used in six major categories namely medicinal use, food, oil-yielding, fibre-yielding, timber, and religious purposes. Out of the 38 important plant species, 25 species were used in medicinal purpose followed by 11 species in religious value, nine plant species were used as food. Tinospora cordifolia, Termnalia bellirica, Terminalia chebula, Azadirachta indica were documented as important medicinal plants. Agave americana, Corchorus depressus, Dracaena roxburghiana, Musa paradisiaca, and Hibiscus sabdariffa were fibre yielding plants. Shorea robusta and Dalbergia sissoo are the important timber plant of the region. The study highlights the Tajpuriya community’s strong dependence on locally available plant resources. It emphasizes the importance of local knowledge regarding the medicinal practices, edible plant species, timber, and other resource utilization patterns, while also underscoring the need for biodiversity conservation and sustainable management.